Edukasi Pengolahan Sampah Organik Rumah Tangga Menjadi Produk Yang Bernilai Ekonomis - Azuxetullatif, Azuxetullatif; Arivetullatif, Arivetullatif; Sulastri, Sulastri; Fathiah, Fathiah; Putri, Maharani; Humaira, Vilma; Mosfika, Eldya (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Household food waste is a type of organic waste that is still a problem in the Bato Village environment. Although food waste is easily decomposed, if it is not managed properly it can trigger environmental problems. Therefore, this community service activity was carried out with the aim of providing education and methods for processing household food waste so that it can become a product with economic value. The method of this community service activity was carried out by delivering educational materials and videos regarding the processing of organic food waste, which was carried out in the multipurpose room of the village head of Bato together with the PKK mothers of Bato Village, Pariaman City. Based on the results of community service, all paticipants were enthusiastic about listening to education on organis waste processing during the series of activities. Participants paid close attention to the video tutorial on the stages carried out for processing household food waste to become H. Illunces fly larvae (maggots). These larvae are a product produced from processing food waste that can be used as feed for fish, such as catfish, tilapia, and gourami. In addition, maggots produced on a large scale can be dried and packaged economically for sale.